Inhibition of lncRNA XIST Improves Myocardial I/R Injury by Targeting miR-133a through Inhibition of Autophagy and Regulation of SOCS2 - Zhiqiang Li; Yaping Zhang; Nan Ding; Yudong Zhao; Zankai Ye; Lei Shen; Hanlu Yi; Yaobin Zhu (Elsevier, 2019)
The objective of this study was to investigate the role of lncRNA XIST and its relationship with miR-133a in myocardial I/R injury. H9C2 cells treated by hypoxia/reoxygenation (H/R) were used to establish an in vitro I/R model. The small interfering RNA (siRNA) for XIST and miR-133 mimics, inhibitor, and suppressor of cytokine signaling (SOCS2) recombinant plasmids were used to transfect the cells. Cell apoptosis was determined by flow cytometry analysis, and cell viability was used for 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide, Thiazolyl Blue Tetrazolium Bromide (MTT) assay. The dual-luciferase reporter assay was performed to confirm binding between XIST and miR-133a, as well as miR-133a and SOCS2. To inhibit or overexpress XIST, miR-133a, or SOCS2 in I/R mice, we used recombinant lentivirus vectors and adenovirus vectors for tail vein injection. The expression of XIST, miR-133a, and SOCS2 was determined by quantitative real-time PCR, and LC3 I/II and Beclin1 was determined by western blotting. The expression of XIST and SOCS2 was significantly upregulated, whereas the miR-133a level was remarkably downregulated in both H/R H9C2 cells and I/R mice myocardial tissues. In both H/R H9C2 cells and I/R mice, the inhibition of XIST led to decreased apoptosis and autophagy, and inhibition of miR-133a reversed these effects. Similarly, overexpression of miR-133a resulted in reduced apoptosis and autophagy, which were reversed by overexpression of SOCS2. The inhibition of XIST and overexpression of miR-133a also promote cell viability of H/R cells. The dual-luciferase reporter assay significantly showed that XIST directly targeted on miR-133a, and miR-133a directly targeted on SOCS2. The inhibition of XIST could improve myocardial I/R injury by regulation of the miR-133a/SOCS2 axis and inhibition of autophagy. Keywords: lncRNA XIST, myocardial ischemic-reperfusion injury, miR-133a, autophagy, SOCS2